Posttraumatic Hydrocephalus: Risk Factors, Treatment Modalities, and Prognosis - Yerramneni, Vamsi Krishna; Kotha, Vamsi Krishna (Indian Journal of Neurosurgery, 2017)
Background Posttraumatic hydrocephalus (PTH) is a rare clinicopathological entity seen as a sequel of head injury (HI). The described incidence in literature is 7 to 29%.Aims and Objectives To study the incidence, risk factors, treatment options, and prognosis.Materials and Methods We retrospectively reviewed our HI database from our institution and identified patients with PTH. The data were obtained from the case files, radiologic records, telephonic interviews, and letters.Results PTH was diagnosed in 32 patients with mean age being 33.7 ± 16.0 years. Severe HI was present in 22(68.75%) patients, and all of them underwent decompressive craniectomy (DC). Remaining patients had either cranial base repair for cerebrospinal fluid (CSF) leak or conservative management. Average duration for development of PTH after the HI was 11.05 ± 0.58 months in DC group and 17.0 ± 1.25 months in the non-DC group. Patients were treated by CSF diversion (ventriculoperitoneal [VP] or thecoperitoneal shunt) and lumbar subarachnoid drainage in the perioperative period of cranioplasty. Average interval between DC and cranioplasty was 6.21 ± 14.0 months. Mean follow-up was 72.23 ± 0.67 months and observed mortality was 32%. Statistical analysis showed correlation between severity of HI, DC, and development of PTH. DC also had correlation with early development of PTH.Conclusion The incidence of PTH is low and the etiology is multifactorial. Severe HI, DC, and delayed cranioplasty (>6 months) are associated with higher chances of PTH development. Though VP shunt placement is the established treatment modality, temporary lumbar subarachnoid drain placement in perioperative period of cranioplasty in selected cases is an option.
Keywords: posttraumatic hydrocephalus; head injury; decompressive craniectomy; cranioplasty; shunt